Production and characterization of lactic acid bacteria biofilms synthesized using tofu wastewater - Atmandaru, Susmaya; Solichah, Amalia; Retnaningrum, Endah (Universitas Gadjah Mada, 2025)
Biofilms serve to protect microbes from environmental conditions. Biofilms produced by lactic acid bacteria (LAB) can even inhibit the growth of pathogens. Medium de Man Ragosa Sharpe (MRS) is a specific medium for LAB growth and biofilm formation; however, it is not effective on an industrial scale due to its high cost. Tofu wastewater serves as an alternative medium because it contains complete nutrients that support the formation of LAB biofilms. This study aimed to determine the effect of C and N formulation in tofu wastewater on the production and characterisation of biofilms produced by four Lactobacillus (LAB) strains, including Enterococcus casseliflavus F4IS5, E. casseliflavus F14IS5, and E. casseliflavus F14IS6. Glucose and ammonium sulfate were added to the tofu wastewater as carbon and nitrogen sources, respectively. The biofilm-forming ability of LAB was tested by the biofilm assay method. The LAB biofilm characteristics were tested based on adhesion, while the exopolysaccharide concentration, a component of the biofilm, was analysed using the dry weight method. The inhibitory activity of LAB biofilms against the growth of pathogenic bacteria, specifically Escherichia coli and Staphylococcus aureus, was tested using the microplate method. The highest LAB biofilm production was obtained from the E. casseliflavus F6IS4 isolate in a tofu wastewater medium supplemented with 2% glucose and 1% ammonium sulfate, with an incubation time of 48 hours. The biofilm produced was categorised as a strong biofilm, which also exhibited strong adhesion; the separate cells accounted for only 19.25%. Besides, the EPS production by the strain was 63.4%. The biofilm of E. casseliflavus F6IS4 in tofu wastewater, supplemented with 2% glucose and 1% ammonium sulfate, also exhibited the highest inhibitory activity against E. coli and S. aureus, at 2.7% and 2.1%, respectively.